2011
DOI: 10.1016/j.cbpb.2011.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a lectin with antibacterial activity from Bothrops leucurus snake venom

Abstract: A novel lectin was isolated from Bothrops leucurus snake venom using a combination of affinity and gel filtration chromatographies. The lectin (BlL) agglutinated glutaraldehyde-treated rabbit and human erythrocytes with preference for rabbit erythrocytes. Galactose, raffinose, lactose, fetal bovine serum and casein inhibited lectin-induced rabbit erythrocyte agglutination. BlL, with a molecular mass of 30 kDa and composed of two subunits of 15 kDa, showed dependence on calcium. BlL is an acidic protein with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 71 publications
4
37
0
3
Order By: Relevance
“…aureus than Gram-negative bacteria such as E. coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Salmonella enteritidis [17]. The difference in the susceptibility of Gram-positive and Gram-negative bacteria may be linked to the difficulty of lectins to cross the Gram-negative bacteria outer cell wall to reach the periplasmic space [15]. Additionally, the high level of peptidoglycan (which contains GlcNac) in the cell wall of Gram-positive bacteria may provide more interaction sites for N-acetyl-glucosamine-binding lectins, such as ClaveLL [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus than Gram-negative bacteria such as E. coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Salmonella enteritidis [17]. The difference in the susceptibility of Gram-positive and Gram-negative bacteria may be linked to the difficulty of lectins to cross the Gram-negative bacteria outer cell wall to reach the periplasmic space [15]. Additionally, the high level of peptidoglycan (which contains GlcNac) in the cell wall of Gram-positive bacteria may provide more interaction sites for N-acetyl-glucosamine-binding lectins, such as ClaveLL [10].…”
Section: Resultsmentioning
confidence: 99%
“…Lectins with potential for biotechnological applications as antibiotics have been isolated and their structures have been characterized [13][14][15]. Lectins are a heterogeneous group of proteins from no immune origin, containing two or more binding sites for mono or oligosaccharides [16].…”
Section: Introductionmentioning
confidence: 99%
“…Guar gel beads produced by cross-linking of refined guar gum (a polysaccharide composed of glucose and mannose) with epichlorohydrin in a mixture of water and 2-propanol (Gupta et al, 1979) have been used to purify galactose-specific lectins Nunes et al, 2011).…”
Section: Lectins: Prototypes In Protein Purification By Affinity Chromentioning
confidence: 99%
“…Snake venoms of the family Viperidae in particular are an important source of peptides, but they remain underexplored (Ferreira et al 2011). Studies have already demonstrated that snake venoms of Bothrops jararaca (Ciscotto et al, 2009), B. leucurus (Nunes et al 2011) B. marajoensis (Costa-Torres et al, 2010), Bothrops alternatus (Bustillo et al, 2008) Crotalus adamanteus (Samy, et al, 2014), C. durissuscumanensis (Vargas et al, 2012) and Porthidium nasutum (Vargas et al, 2013) have antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%